Effect of Beta-Blocker Therapy on Rehospitalization Rates in Women Versus Men With Heart Failure and Preserved Ejection Fraction - Farasat, S. Morteza; Bolger, Dennis T.; Shetty, Veena; Menachery, Elizabeth P.; Gerstenblith, Gary; Kasper, Edward K.; Najjar, Samer S. (The American journal of cardiology, 2010)
Beta blockers are empirically used in many patients with heart failure (HF) and preserved ejection fraction (HFpEF) because they allow more time for diastolic filling and because they improve outcomes in patients with systolic HF. However, recent data suggest that impaired chronotropic and vasodilator responses to exercise, which can worsen with β blockade, may play a key role in the pathophysiology of HFpEF. We prospectively examined the association between β-blocker therapy after hospitalization for decompensated HF and HF rehospitalization at 6 months in 66 consecutive patients with HFpEF (71 ± 13 years old, 68% women, 42% Black). Subjects were stratified based on receiving (BB+; 15 men, 28 women) or not receiving (BB−) β-blockers at hospital discharge. In men, HF rehospitalization occurred less frequently in the BB+ than in the BB− group, albeit nonsignificantly (20% vs 50%, p = 0.29). In women, HF rehospitalization occurred more frequently in the BB+ than in the BB− group (75% vs 18%, p <0.001). In univariate analyses, discharge β-blocker was associated with HF rehospitalization in women (odds ratio [OR] 14.00, 95% confidence interval [CI] 3.09 to 63.51, p = 0.001), but not in men (OR 0.25, 95% CI 0.03 to 1.92, p = 0.18). In a forward logistic regression model that offered all univariate predictors of HF rehospitalization, discharge β blocker remained an independent predictor of HF rehospitalization in women (OR 11.06, 95% CI 1.98 to 61.67, p = 0.006). In conclusion, this small observational study suggests that β-blocker therapy may be associated with a higher risk of HF rehospitalization in women with HFpEF. The risks and benefits of β-blocker therapy in patients with HFpEF should be evaluated in randomized, controlled trials.